Using the RNAstructure Software Package to Predict Conserved RNA Structures. Issue 1 (17th June 2014) - Mathews, David H.
Abstract: The structures of many non‐coding RNA (ncRNA) are conserved by evolution to a greater extent than their sequences. By predicting the conserved structure of two or more homologous sequences, the accuracy of secondary structure prediction can be improved as compared to structure prediction for a single sequence. This unit provides protocols for the use of four programs in the RNAstructure suite for prediction of conserved structures, Multilign, TurboFold, Dynalign, and PARTS. These programs can be run via Web servers, on the command line, or with graphical interfaces. Curr. Protoc. Bioinform . 46:12.4.1‐12.4.22. © 2014 by John Wiley & Sons, Inc.